The Effectiveness of Application of Funeral Service Information Systems in the City of Bandung - Bayu Eka Lesmana (Department of Public Administration, 2023)
To optimize funeral services in the city of Bandung, the Bandung city government through the Cipta Karaya, Construction and Spatial Development Services (Ciptambintar) launched a Funeral Service Information System (Simpelman). Which aims to provide convenience and acceleration of funeral services that were originally conventional to digital or application-based. The research method used in this writing is a descriptive research method with a qualitative approach, the data contained in this study comes from primary data obtained directly from the results of research in the field through interviews and secondary data obtained from relevant literary documents such as journal articles, books to legislation. The Simpelman application can be said to have been effective in its application, this can be proven by the readiness of the Bandung city government in the construction of the Simpelman system accompanied by supporting factors.